ANALISIS FAKTOR-FAKTOR PENENTU INFLASI DI INDONESIA - Rando, Sirtal Sirtalya. J; Rotinsulu, Debby Ch.; Rorong, Ita Pingkan Fasnie (JURNAL PEMBANGUNAN EKONOMI DAN KEUANGAN DAERAH, 2021)
ABSTRAKSalah satu persoalan yang sering terjadi di negara yang berkembang adalah pertumbuhan dan stabilitas ekonominya. Stabilitas ekonomi dimaksud tersebut menyangkut Stabilitas harga, Stabilitas pendapatan, dan pertambahan kesempatan kerja, serta Stabilitas politik. Dalam perekonomian yang cenderung â€œmemanasâ€ (overheating) kebijakan moneter maupun kebijakan fiskal bersifat kontraktif, sedangkan pada kondisi ekonomi yang â€œstagnanâ€ kebijakan moneter dan kebijakan fiskal yang efektif adalah kebijakan yang ekspansif. Secara logis, Nilai tukar, pengeluaran pemerintah berpengaruh positif terhadap inflasi. sedangkan kenaikan tingkat suku bunga akan menurunkan jumlah uang beredar dan berpengaruh negatif terhadap tingkat inflasi. Jumlah uang beredar berpengaruh negatif terhadap inflasi akan tetapi tidak signifikan secara statistik. Hasil penelitian suku bunga, nilai tukar, pengeluaran pemerintah dan jumlah uang beredar secara bersama-sama memiliki pengaruh yang signifikan terhadap inflasi.Â Kata Kunci : Inflasi, Suku Bunga, Nilai Tukar, Jumlah Uang beredar dan Pengeluaran PemerintahÂ ABSTRACTOne of the problems that often occurs in developing countries like Indonesia is maintaining stability and economic growth. This economic stability concerns the stability of the price level, the level of national income, and the growth of employment opportunities. The government can implement a series of policies in an effort to stabilize the economy. For example, monetary policy and fiscal policy, which aims to achieve a stable price level or inflation rate. The purpose of this study was to see the effect of interest rates, exchange rates, government spending and the amount of money in circulation on inflation. The research method used is multiple regression with the analysis tool Eviews 8. The results showed that the SBI interest rate had a positive and significant effect on inflation in Indonesia. The exchange rate has a positive influence on inflation. That is, if the exchange rate rises, inflation will increase cateris paribus. Government Expenditures has a positive relationship to inflation but is not statistically significant. The money supply has a negative effect on inflation but is not statistically significant. The results of the research on interest rates, exchange rates, government spending and the money supply together have a significant effect on inflation.Â Keywords: Inflation, Interest Rates, Exchange Rates, Money Supply and Government Expenditures